دور التسويق بالعلاقات في تعزيز الميزة التنافسية لشركات الـتأمين دراسة ميدانية في محافظة اللاذقية - قاسم, سامر; كنعان, علي (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يهدف البحث إلى التعرف على دور التسويق بالعلاقات في تعزيز الميزة التنافسية لشركات التأمين, وذلك من خلال دراسة العلاقة بين أبعاد التسويق بالعلاقات, والمتمثلة بـ: الثقة, التفاعل, الالتزام, الاتصال, الولاء, وتعزيز الميزة التنافسية. اعتمد البحث المنهج الوصفي, وشمل مجتمع البحث العملاء الذين راجعوا شركات التأمين في محافظة اللاذقية خلال فترة تطبيق البحث, والبالغة ثلاثة أشهر, حيث قام الباحث خلال هذه الفترة بتوزيع (185) استبانة على العملاء بشكل عشوائي, وذلك لاستقصاء آرائهم حول دور التسويق بالعلاقات في تعزيز الميزة التنافسية في شركات التأمين التي يتعاملوا معها, وتمّ استعادة (173) استبانة كاملة وصالحة للتحليل الإحصائي, وبنسبة استجابة بلغت (93.51%). وبالاعتماد على الانحدار البسيط في تحليل وإظهار العلاقة بين متغيري البحث توصل البحث إلى وجود علاقة طردية ذات دلالة معنوية بين كل بعد من أبعاد التسويق بالعلاقات, وتعزيز الميزة التنافسية في الشركات محل الدراسة, حيث أنّ الأداء التسويقي الجيد للشركات محل الدراسة أمكنها الحفاظ على زبائنها الحاليين, واكتساب زبائن جدد, وتحقيق معدلات نمو في المعاملات مع هؤلاء الزبائن من خلال بناء علاقات معهم أساسها تحقيق رضاهم وتقديم سلع وخدمات ذات قيمة كبيرة.The research aims to identify the role of Relationship Marketing in enhancing the competitive advantage of insurance companies, through the study of the relationship between the dimensions of marketing relations, represented by: trust, interaction, commitment, communication, loyalty, and strengthen competitive advantage. Adopted Find descriptive approach, which included the research community customers who reviewed the insurance companies in Latakia province during the period of application of research, amounting to three months, with the researcher during this period distributed (185) to identify customers at random, so as to explore their views on the role of Relationship Marketing in promoting competitive advantage in the insurance companies that deal with it, and was restored (173) to identify complete and valid for statistical analysis, and response rate (93.51%). Based on simple regression analysis and show the relationship between the two variables Search reach and there is a significant moral positive correlation between each dimension of marketing dimensions of relations, and enhance the competitive advantage of companies in the study, since the marketing performance of good companies under study been able to keep existing customers, and the acquisition of new customers, and to achieve growth rates in transactions with these customers by building relationships with them based achieve satisfaction and provide goods and services of great value.